Impact of hull flexibility on the global performance of a 15 MW concrete-spar floating offshore wind turbine - Lee, Ikjae; Kim, Moohyun; Jin, Chungkuk (Marine structures, 2025)
•The impact of the hull flexibility of a 15MW spar-type floating offshore wind turbine (FOWT) on the global performance analysis has been investigated based on discrete-module-based (DMB) modeling of the spar hull.•Free-decay, free-vibration, irregular wave white-noise, and various design load cases (DLCs) in parked and operating conditions were examined for both rigid- and flexible-hull FOWT numerical models with catenary and taut mooring systems, and the numerical results were systematically compared with each other.•The lowest bending mode natural frequency is substantially shifted down from 0.52 Hz to 0.41 Hz. The shifted natural frequency is more likely to resonate in operational conditions, leading to appreciable increases in horizontal nacelle accelerations and tower-base bending moments. In this study, we investigated the impact of the hull flexibility of 15MW spar-type FOWT (floating offshore wind turbine) on the global dynamics/performance analysis. Until recently, the rigid hull (floating foundation) model with flexible tower and RNA (rotor-nacelle assembly) has been used as industry standard procedure in the global performance analysis of FOWTs. Since the FOWT size continues to increase beyond 20MW, there has been increasing concern of the effect of hull flexibility on its global performance. The present study is intended to provide representative insights on this subject. Global performance analysis of the 15MW WindCrete spar is examined based on the conventional hull-rigid and the DMB (discrete-module-beam) models including hull flexibility. Coupled aero-hydro-servo-elastic-mooring dynamic simulations were carried out with the rigid-hull and DMB (discrete-module-beam) models under various combinations of irregular waves, sheared currents, and full-field turbulent winds. The lowest fore-aft bending-mode natural frequency is shifted toward lower frequency from 0.52 to 0.41 Hz after including hull flexibility. Platform rigid 6-DOF (degree-of-freedom) motions and mooring tensions by the DMB model are little changed but nacelle horizontal accelerations and tower-base bending moments may be appreciably increased compared to the rigid-hull model.